Demonstration of laser pulse amplification by stimulated Brillouin scattering. (1st September 2014) - Guillaume, E.; Humphrey, K.; Nakamura, H.; Trines, R. M. G. M.; Heathcote, R.; Galimberti, M.; Amano, Y.; Doria, D.; Hicks, G.; Higson, E.; Kar, S.; Sarri, G.; et al.
Abstract: The energy transfer by stimulated Brillouin backscatter from a long pump pulse (15 ps) to a short seed pulse (1 ps) has been investigated in a proof-of-principle demonstration experiment. The two pulses were both amplified in different beamlines of a Nd:glass laser system, had a central wavelength of 1054 nm and a spectral bandwidth of 2 nm, and crossed each other in an underdense plasma in a counter-propagating geometry, off-set by #1#1#1=≤ ==≥ =PrFrRe10^° . It is shown that the energy transfer and the wavelength of the generated Brillouin peak depend on the plasma density, the intensity of the laser pulses, and the competition between two-plasmon decay and stimulated Raman scatter instabilities. The highest obtained energy transfer from pump to probe pulse is 2.5%, at a plasma density of 0.17 n_cr, and this energy transfer increases significantly with plasma density. Therefore, our results suggest that much higher efficiencies can be obtained when higher densities (above 0.25 n_cr ) are used.